Mobile Application for Inventory Control in a Minimart - Darnis, Febriyanti (Bina Nusantara University, 2017)
The goal of the research was to design a mobile application of inventory system in a minimart. In an application of using the mobile-based inventory minimart, J2EE system development used Waterfall method with the stages of analysis, design, coding, and implementation. The control of application inventory items at the minimart was intended for mobile-based users who controlled the supply of goods on the markets. It was to facilitate employee minimart in organizing, processing, monitoring the movement of inventory items that occurred in the minimart. The application of control inventory-based mobile minimart was to make users inventory, with a menu that was available in the form of product items, a promotion that had a limited promotion item reservations. The application can make employees in a minimart organize, process, and monitor the movement of inventory item more easily.